2019
DOI: 10.1111/1750-3841.14453
|View full text |Cite
|
Sign up to set email alerts
|

A Fluorescence‐based Method for Estimation of Oxygen Barrier Properties of Microspheres

Abstract: In this study, we developed a fluorescence method to quantify oxygen barrier properties for wall materials used in microencapsulation of oxygen‐sensitive compounds. We used a reversible, oxygen quenching dye, tris (4,7‐diphenyl‐1, 10‐phenanthroline) ruthenium(II) dichloride complex, as a marker to monitor oxygen transport across spray‐dried and freeze‐dried Hi‐cap100 and maltodextrin microspheres. We fit the rate of oxygen transport to Fick's second law and extrapolated an effective oxygen diffusion coefficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…The values of D eff fall within the range of previous studies, which ranged from 6.46 × 10 −15 m 2 s −1 -22.4 × 10 −15 m 2 s −1 for microcapsules equilibrated at a w = 0.33 (Kak et al, 2019). In particular, Kak et al (2019) reported the D eff for Hi-cap100/MD 23 (1:2) microcapsules as 16.7 × 10 −15 m 2 s −1 , which is similar to that of MD 26 microcapsules. Although GA is generally known to have a poorer oxygen barrier than Hi-cap 100, due to presence of higher concentration of MD present in this study, the D eff for prepared microcapsule is similar to the previously reported range (Carneiro et al, 2013;Granados-Vallejo et al, 2019).…”
Section: Oxygen Diffusion Coefficientsupporting
confidence: 85%
See 3 more Smart Citations
“…The values of D eff fall within the range of previous studies, which ranged from 6.46 × 10 −15 m 2 s −1 -22.4 × 10 −15 m 2 s −1 for microcapsules equilibrated at a w = 0.33 (Kak et al, 2019). In particular, Kak et al (2019) reported the D eff for Hi-cap100/MD 23 (1:2) microcapsules as 16.7 × 10 −15 m 2 s −1 , which is similar to that of MD 26 microcapsules. Although GA is generally known to have a poorer oxygen barrier than Hi-cap 100, due to presence of higher concentration of MD present in this study, the D eff for prepared microcapsule is similar to the previously reported range (Carneiro et al, 2013;Granados-Vallejo et al, 2019).…”
Section: Oxygen Diffusion Coefficientsupporting
confidence: 85%
“…Although the moisture content was not measured for the equilibrated microcapsules, the moisture content estimated from reported sorption isotherms of MD and GA may be in the range of 8.0–8.5% (Ahmed & Abdelgadir, 2014; Nurhadi et al ., 2016). The values of D eff fall within the range of previous studies, which ranged from 6.46 × 10 −15 m 2 s −1 –22.4 × 10 −15 m 2 s −1 for microcapsules equilibrated at a w = 0.33 (Kak et al ., 2019). In particular, Kak et al .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Concept of microencapsulation based on formation of protective barrier around the active ingredient and widely deployed in improvement and preservation of biological and functional element of food (Ray et al, 2016). Microencapsulation functions as a vehicle that carry active components, prevent oxidation and mask the properties like odor and taste that are not desired, so there is extensive use of this technique in food-based industries (Kak et al, 2019).…”
Section: Wetabilitymentioning
confidence: 99%